Differences in dental caries experience between diabetic adolescents and healthy controls (Journal of Health Sciences, 2016)
Introduction: While the influence of type 1 diabetes mellitus (T1DM) on periodontal health is well established, results of previous studies regarding the association of this metabolic disease and caries experience are rather inconsistent. The aim of this study was to assess the differences between caries status of healthy and adolescents with T1DM, as well as to determine the differences in caries experience among diabetic patients in relation to their metabolic control.Methods: Assessment of caries status was performed using the DMFT index (decayed, missing, and filled teeth). The study group (Diabetic) included 60 patients diagnosed with T1DM, aged 12-18 years, from Sarajevo Canton. This group was divided into two sub-groups: a sub-group Diabetic-W consisted of 30 patients with well-controlled glycaemia, while a subgroup Diabetic-P comprised of 30 patients with poorer glycemic control. The control group consisted of 30 age-matched metabolically healthy individuals.Results: The T1DM adolescents had a significantly higher (p < 0.01) mean DMFT score than the healthy subjects, 11.49 and 6.19 respectively. Statistically, the diabetic group had also significantly higher values of the D and M components. Concerning the metabolic control, mean DMFT score in the Diabetic-W subgroup was lower (10.57) than in the Diabetic-P subgroup (12.39), however the difference was not statistically significant.Conclusions: The results demonstrate that the T1DM patients have a higher caries experience, regardless of the degree of metabolic control. The level of untreated dental decay and missing teeth components among the diabetic adolescents indicates irregular dental attendance.